Perancangan Alat Tekanan Darah Otomatis secara Berkala menggunakan Sensor MPX5050DP untuk Pasien Hipertensi - Afdhal Kurniawan; Karli Eka Setiawan (LPPM STT Terpadu Nurul Fikri, 2023)
Regular blood pressure monitoring is crucial in caring for outpatient patients undergoing treatment. Hypertension, commonly known as high blood pressure, is a prevalent medical condition that can increase the risk of heart disease, stroke, and other vascular disorders. Patients with hypertension often require regular blood pressure measurements to monitor their health status and evaluate the effectiveness of ongoing treatment. To mitigate the risks associated with hypertension, routine health check-ups, including periodic blood pressure measurements at home, can be taken. This research aims to make a regular automatic blood pressure meter to help hypertensive patients. The design of an automatic periodic blood pressure measurement device using the MPX5050DP sensor for hypertensive patients is expected to facilitate regular monitoring and assist doctors in making accurate diagnoses. Research results indicate a larger error percentage for diastolic values than systolic values. Specifically, the error percentage is 3.45% for systolic values and 7.17% for diastolic values.